Magnetoelectric micromachines with wirelessly controlled navigation and functionality. Issue 2 (15th December 2015) - Chen, Xiang-Zhong; Shamsudhin, Naveen; Hoop, Marcus; Pieters, Roel; Siringil, Erdem; Sakar, Mahmut Selman; Nelson, Bradley J.; Pané, Salvador
Abstract : A magnetoelectric micromachine manipulated by magnetic field for both locomotion and on-demand function triggering enlighten the concept of unisource-powered microdevices. Abstract : The use of a single energy source for both manipulating micromachines and triggering their functionalities will result in highly integrated devices and simplify the design of the controlling platform. Here, we demonstrate this concept employing magnetoelectric Janus particle-based micromachines, which are fabricated by coating SiO2 microspheres with a CoFe2 O4 –BaTiO3 bilayer composite. While the inner magnetic CoFe2 O4 layer enables the micromachines to be maneuvered using low magnitude rotating magnetic fields, the magnetoelectric bilayer composite provides the ability to remotely generate electric charges upon the application of a time-varying magnetic field. To demonstrate the capabilities of these micromachines, noble metals such as Au, Ag and Pt are magnetoelectrochemically reduced from their corresponding precursor salts and form nanoparticles on the surface of the micromachines. Magnetoelectric micromachines are promising devices for their use as metal scavengers, cell stimulators and electric field-assisted drug delivery agents.